INTERVENSI MULLIGAN BENT LEG RAISE EXERCISE LEBIH BAIK DARI PADA MC. KENZIE EXTENSION EXERCISEDALAM MENURUNKANNYERI DAN DISABILITAS PADA KASUS NYERI PINGGANG MIOGENIK DI RS.BAYUKARTA (Lembaga Penerbitan Universitas Esa Unggul, 2017)
AbstractObject : to prove Mulligan bent leg raise is better than Mc. Kenzie extension exercise to reduce pain and disability in miogenik low back pain. Methods : experimental. Sampel are 10 employers at Bayukarta hospital. Choosen by purposive sampling.Results : after 12 times exercise. Hypothesis I using paired sample t-test obtained VAS average before (58.40±3.91) and after (35.00±5.61) then p =0.001 and ODI average before (38.80±2.28) and after (21.00±8.94) then p =0.006 which means Mulligan bent leg raise can reduce pain and disability. Hypothesis II using paired sample t-test obtained VAS value before (57.20±7.62) and after (37.60±8.20) then p< 0.001 and ODI using Wilcoxon test, average before (44.80±5.01) and after (30.80±8.43) then p=0.042 which means Mc. Kenzie extension exercise can reduce pain and disability. On hypothesis III using Mann Whitney u-test obtained ODI average difference of one (21.00±8.94) and two (30.80±8.43) then p = 0.249 and VAS using independent t-test obtained after one (58.40±3.91) and two (57.20 ±7.62) p=0.575 which meaning Mulligan bent leg raise is not better than Mc. Kenzie extension exercise. Conclution: Mulligan bent leg raise is not better than Mc. Kenzie extension exercise to reduce pain and disability in miogenik low back pain at Rs. Bayukarta. Keywords : Mulligan bent leg raise exercise, Mc. Kenzie extension exercise, pain, disability.AbstrakTujuan :Untuk membuktikan intervensi Mulligan bent leg raise exercise lebih baik dari pada Mc. Kenzie extension exercisedalam menurunkannyeri dan disabilitaspada nyeri pinggangmiogenik. Metode :eksperimental.10 sampel pegawaidi RS.Bayukarta,tekniknyapurposive sampling.Hasil : setelah 12 kali latihan. Hipotesis I menggunakanpaired sample t-test, VAS rerata sebelum (58.40±3.91) dan sesudah (35.00±5.61)maka p=0.001danODI rerata sebelum (38.80±2.28)dan sesudah (21.00±8.94) maka p=0.006berartiintervensiMulligan bentlegraisedapatmenurunkannyeridandisabilitas. Hipotesis II menggunakanpaired sample t-testdanWilcoxon testdidapatkanVAS rerata sebelum (57.20±7.62) dan sesudah (37.60±8.20)maka p<0.001dan ODI rerata sebelum (44.80±5.01)dan sesudah (30.80±8.43) makap= 0.042 berartiintervensiMc. Kenzie extension exercisedapatmenurunkannyeridandisabilitas. Hipotesis III menggunakanMann Whitneyu-test,ODI rerata selisih 1 (21.00±8.94) dan 2 (30.80±8.43) maka p=0.249dan VAS menggunakanindependen t-test didapat rerata sesudah 1 (58.40±3.91) dan 2 (57.20 ±7.62) maka p=0.575 yang berartiintervensiMulligan bentlegraisetidak lebihbaikdaripadaMc. Kenzie extension exercisedalammenurunkannyeridandisabilitas. Kesimpulan :IntervensiMulligan bentlegraisesama baiknya denganMc. Kenzie extension exercise dalam menurunkan nyeri dan disabilitas pada kasus nyeri pinggang miogenik di Rs.Bayukarta. Kata Kunci :Mulligan bent leg raise exercise, Mc. Kenzie extension exercise,nyeri, disabilitas.